PENGARUH PERSEPSI KUALITAS DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN GENERASI Z DI KOTA SEMARANG MELALUI MINAT BELI PADA SMARTPHONE XIAOMI - Dimas Rizky Sutikno; Elia Resha Fatmawati; Diana Aqmala; Febrianur Ibnu Fitroh Sukono Putra (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to examine how perceived quality and price shape purchase decisions of Generation Z consumers in Semarang City when buying Xiaomi smartphones, both directly and through the mediating role of purchase intention. The rapid development of technology and the increasing reliance on smartphones among young consumers make it important to understand the behavioral factors behind their purchasing choices.Methods: This research is a quantitative approach; data were collected from 140 respondents who had purchased a Xiaomi smartphone. The analysis was conducted using SmartPLS 4 to evaluate measurement validity, structural relationships, and hypothesis testing.Results: The results indicate that perceived quality and price have a positive and significant effect on purchase intention. Furthermore, perceived quality also significantly influences purchase intention indirectly through the mediating role of purchase intention, demonstrating partial mediation in the relationship between perceived quality and purchase decision. These findings suggest that Generation Z consumers place strong emphasis on the evaluation of product quality and price suitability before forming purchase intention and making final purchase decisions. Based on the results, it is recommended that Xiaomi focus on strengthening consumers’ perceived quality and maintaining competitive pricing strategies to enhance purchase intention and purchasing decisions among Generation Z consumers. Conclusion and suggestion: These findings indicate that perceived quality and price significantly influence purchase decisions, both directly and through purchase intention as a partial mediator. Keywords: Perceived Quality, Price, Purchase Decision, Purchase Intention,